Geometrically nonlinear regularized extended finite element analysis of compression after impact in composite laminates. (July 2020) - McQuien, Jeffrey S.; Hoos, Kevin H.; Ferguson, Lauren A.; Iarve, Endel V.; Mollenhauer, David H.
Abstract: The geometrically nonlinear Rx-FEM formulation was applied to compression after impact (CAI) strength prediction. The impact-induced damage including permanent out-of-plane dent, delaminations, and matrix cracks were included into the analysis domain prior to application of compressive loading. While the inclusion of the dent and delaminations was based directly on provided information, impact-induced matrix cracks were incorporated into the analysis configuration by application of a pseudo-impact load prior to CAI. The resulting matrix cracks matched the accompanying delamination patterns in a consistent manner. Influence of several parameters and their combinations on CAI strength prediction was performed. It was found that accounting for the thermal residual stresses introduced additional buckling instability similar to that of the dent and allowed accurate prediction without simulating the dent. Two approximate delamination patterns representative of time-of-flight C-scan and tap-test inspection results were examined and found to be reasonably conservative with 9% and 14% margins, respectively.